Local vegetation history of Norway spruce (Picea abies (L.) Karst.) in central Scandes (Sweden) since the mid-Holocene - Garrido Rodriguez, Pablo (SLU/Dept. of Forest Ecology and Management, 2008)
The former migration theory of Norway spruce (Picea abies (L.) Karst.) suggested that spruce established in Sweden along the Swedish Bothnian coast c. 3500 years ago from an eastern refuge area through Finland. Recent spruce megafossil finds of Late Glacial and early Holocene in west central Sweden have challenged this theory suggesting a much earlier immigration and a possible western migration route.